Auditory p300 in noise in younger and older adults - McCullagh, Jennifer; Shinn, Jennifer B. (Journal of the American Academy of Audiology, 2018)
Background: Older adults often report difficulty hearing in background noise which is not completely attributable to peripheral hearing loss. Although age-related declines in cognition and hearing in back-ground noise occur, the underlying age-related changes in processing of auditory stimuli in background noise has yet to be fully understood. The auditory P300 has the potential to elucidate the effects of age on auditory and cognitive processing of stimuli in background noise, but additional research is warranted. Purpose: The purpose of this study was to investigate age-related differences in cognitive processing of auditory stimuli by evoking the auditory P300 at multiple signal-to-noise ratios (SNRs). Research Design: A two-group, repeated measures study design was used. Study Sample: A convenience sample of 35 participants, 15 older adults (mean age of 66.4 yr) and 20 younger adults (mean age of 21.1 yr), participated in the study. All participants had negative otologic and neurological histories. Data Collection and Analysis: The auditory P300 was evoked using an oddball paradigm with 500 (frequent) and 1000 Hz (target) tonal stimuli in quiet and in the presence of background noise at +20, +10, and 0 SNRs. P300 amplitudes and latencies were measured in each condition for every participant. Repeated measures analyses of variance were conducted for the amplitude and latency measures of the P300 for each group. Results: Results from this study demonstrated P300 latencies were significantly longer in older adults in noise at the most challenging condition (0 SNR) compared with the quiet condition and between the +10 SNR and 0 SNR conditions. Although older adults had significantly longer P300 latencies compared with younger adults, no significant group by listening condition interaction existed. No significant P300 amplitude differences were found for group, noise, or group x listening condition interactions. Conclusions: Results provide evidence that auditory cortical processing, regardless of age, is poorer at more difficult SNRs. However, results also demonstrate that older adults perform significantly poorer than younger adults. This supports the notion that some degree of age-related decline in synchronous firing and rate of transmission of the auditory cortical neurons contributing to the auditory P300 exists. Studies are needed to further understand the impact of noise on auditory cortical processing across populations.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000467875700005 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Acoustic Stimulation; Aged; Aging; Auditory Cortex; Auditory Perception; Auditory Threshold; Cognition; Conference Paper; Evoked Potentials; Auditory; Female; Hearing in noise; Humans; Male; P300; Reference Values; Young Adult; adult; aged; auditory cortex; auditory evoked potential; auditory stimulation; auditory threshold; brain cell; clinical article; cognition; comparative study; convenience sample; dept.cmd; female; hearing; hearing acuity; hearing impairment; human; latent period; male; medical history; mental deterioration; noise; otoscopy; outcome assessment; peer-reviewed; physiology; priority journal; procedures; pure tone audiometry; reference value; signal noise ratio; white noise; working memory; young adult